Investigation of recurrent case of salmonellosis due to salmonella bovismorbificans and salmonella matopeni using pulsed-field gel electrophoresis analysis and antibiograms - Thong, Kwai Lin; Puthucheary, Savithri Devi; Boey, C.C.M.; Pang, Tikki (Faculty of Medicine, University of Malaya, 1999)
A restropective study on a case of recurent salmonellosis in a 3 month old child due to Salmonella bovismorbificans and S. matopeni was carried out using pulsed field gel electrophoresis (PFGE) and susceptibility analysis. PFGE clearly distinguished the two serovars and that the recurrent infection was shown to associated with variant forms of S. bouts:-irorbtficnns. The chromosomal changes detected among the sequential isolates of S. bovismorbificans appeared to be associated with varing antibiogram patterns. The study also showed that the recurrent infection in the patient could be related to prolonged antibiotic therapy.